Developing Porous Honeycomb Films Using Miktoarm Star Copolymers and Exploring Their Application in Particle Separation. Issue 2 (23rd September 2013) - Zhang, Chengyi; Wang, Xiaofeng; Min, Ke; Lee, Doyun; Wei, Chuan; Schulhauser, Hannah; Gao, Haifeng; Lutz, J.‐F.; Sumerlin, B.; Matyjaszewski, K.
<x xml:space="preserve">Abstract</x> This paper reports for the first time the synthesis and application of miktoarm star copolymers to produce highly ordered honeycomb films using the breath figure technique. Miktoarm star copolymer containing a cross‐linked core and two arm species, e.g., polystyrene and poly(t‐butyl acrylate), is successfully synthesized using ATRP in a one‐pot arm‐first method. Various experimental parameters, including polymer architectures, solvents, polymer concentrations, and substrates, are explored to investigate their effects on the structure of the honeycomb films. It is found that miktoarm star copolymers with high molecular weight and spherical shape could readily produce ordered honeycomb films in a broader range of concentrations and humidity than linear block copolymers with similar chemical compositions but lower molecular weight. Partial hydrolysis of poly(t‐butyl acrylate) arm species in the honeycomb film transforms the surface property from hydrophobic to hydrophilic while maintaining the film's mechanical stability in water. This porous monolayer film with uniform pore size distribution and inter‐connected pore channels is successfully applied for separation of microparticles with different sizes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>